Relationship Between Nutritional Status and Blood Sugar Levels with Wound Healing in Diabetic Ulcer Patients in the Stoma Wound Care Center Nursing Practice, Incontinence Wound Care Center Medan in 2025 - Yusridawati (Benih : Journal of Midwifery, 2025)
Chronic wounds as wounds that do not heal within the expected time or heal very slowly, often require a comprehensive approach to their management. Factors such as nutritional status and blood sugar levels play an important role in the wound healing process. The purpose of the study The Relationship Between Nutritional Status and Blood Sugar Levels with Wound Healing in Diabetic Ulcer Patients in the Stoma Wound Care Center Nursing Practice, Incontinence Wound Care Center Medan in 2025. This type of research is descriptive correlation, with a cross-sectional research design. The population in this study were all patients with diabetic ulcers as many as 300 people. The sampling technique is Acidental sampling, with a time of 2 weeks, the number of samples is 30 people, data is taken through observation sheets, measurement of nutritional status, blood sugar levels, and wound healing, data is processed through the Spearman rank test. The results of the study found that the majority of normal nutritional status was 24 people (80.0%), high blood sugar levels as many as 30 people (100.0%), healing of minor wounds as many as 29 people (96.6%), the results of the Spearman rank test of the relationship between nutritional status and wound healing are p (value) = 0.002 (<0.05) so that Ha is accepted which means there is a relationship between nutritional status and wound healing and a relationship between blood sugar levels and wound healing, namely p (value) = 0.003 (<0.05) so that Ha is accepted which means there is a relationship between blood sugar levels and wound healing. The results of this study are the relationship between nutritional status and blood sugar levels with wound healing in diabetic ulcer patients at the Stoma Wound Care Center Nursing Practice, Incontinence Wound Care Center Medan in 2025, it is expected to provide a valuable contribution to improving the quality of health services at the research site, especially in the care of diabetic ulcer patients.